Phase transition, dielectric and piezoelectric properties of Li xK1-x NbO3 - Machado, Rodrigo (2014)
The influence of Li impurities on the phase transition, dielectric and piezoelectric properties of KNbO3 ceramics is investigated. We found that Li doping alters the transition temperatures of KNbO3. While the temperature for the orthorhombic–tetragonal phase transition decreases, the temperature of the cubic–tetragonal ferroelectric phase transition increases. The dielectric and piezoelectric properties of the ceramics are improved by the addition of Li. The experiments were contrasted and complemented with first-principles-based atomic level simulations to gain more insight into the intrinsic properties of the solid solution. We show that the impurities improve the dielectric properties due to a relaxational contribution of the off-center Li ions. The increase of the piezoelectric response is associated to the concentration dependence of the shear piezoelectric coefficients.